2017
DOI: 10.4049/jimmunol.1700315
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 Improves the Resolution of Inflammation via Activating NF-κB p50/p50–Mediated Cyclooxygenase-2 Expression in Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a severe illness characterized by uncontrolled inflammation. The resolution of inflammation is a tightly regulated event controlled by endogenous mediators, such as resolvin D1 (RvD1). Cyclooxygenase-2 (COX-2) has been reported to promote inflammation, along with PGE2, in the initiation of inflammation, as well as in prompting resolution, with PGD2 acting in the later phase of inflammation. Our previous work demonstrated that RvD1 enhanced COX-2 and PGD2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 69 publications
(71 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, stimulated alveolar macrophages had reduced concentrations of ARA-derived mediators, such as PGE2 and TXB2, suggesting a beneficial effect of omega-3 fatty acids over omega-6 fatty acids in ALI attenuation [77,78]. More recently, the role of SPMs, specifically resolvins, in the resolution of inflammation has been demonstrated in several animal models of ALI and ARDS [79][80][81][82]. These studies, carried out using rats and mice models infected with E.coli O55:B5 endotoxin LPS, suggested that the pro-resolving effects of these molecules could be attributed, for example, to the suppression of neutrophil infiltration due to reduction of expression and release of pro-inflammatory cytokines from alveolar macrophages [79,81].…”
Section: Evidence Of Omega-3 Fatty Acids Supplementation On Inflammatmentioning
confidence: 98%
“…Furthermore, stimulated alveolar macrophages had reduced concentrations of ARA-derived mediators, such as PGE2 and TXB2, suggesting a beneficial effect of omega-3 fatty acids over omega-6 fatty acids in ALI attenuation [77,78]. More recently, the role of SPMs, specifically resolvins, in the resolution of inflammation has been demonstrated in several animal models of ALI and ARDS [79][80][81][82]. These studies, carried out using rats and mice models infected with E.coli O55:B5 endotoxin LPS, suggested that the pro-resolving effects of these molecules could be attributed, for example, to the suppression of neutrophil infiltration due to reduction of expression and release of pro-inflammatory cytokines from alveolar macrophages [79,81].…”
Section: Evidence Of Omega-3 Fatty Acids Supplementation On Inflammatmentioning
confidence: 98%
“…This could be very important in the context of severe COVID-19 which manifests as uncontrolled inflammation, the so-called cytokine storm [18,19], linked with acute respiratory distress syndrome (ARDS). A number of the SPMs formed from EPA and DHA have been shown in animal models to both protect against and resolve acute lung injury and ARDS [20][21][22][23][24]. Nutritional formulas containing antioxidants and rich in EPA and DHA have been used in several human trials of patients with ARDS.…”
Section: Nutritional Impact On Immunitymentioning
confidence: 99%
“…Inflammasome activation is also dependent on the upregulation of NF-κB [ 297 , 299 ]. Importantly there is an accumulating body of evidence implicating elevated NF-κB in the pathogenesis and progression of ARDS [ [300] , [301] , [302] , [303] ].…”
Section: A Suggested Therapeutic Approach To Treatmentmentioning
confidence: 99%